REPRESENTASI PERILAKU BERMEDIA MELALUI IDENTITAS BUDAYA ETNIS TIONGHOA PASCA REFORMASI DALAM BERITA DUKACITA - Dodot Sapto Adi (SEMIOTIKA: Jurnal Komunikasi, 2016)
Newspaper and advertising is an integral and inseparable. Most of the audience considers the obituary is an ad in the newspaper. This is because, to buy the obituary columns in newspapers can inform proclaim the death of the family. And the use of these columns is Chinese citizens. As well known community, which in modern society and the election of the trend of using the mass media reflects the status of their lives. Mostly, in their real live, the Chinese community use obituary to deliver message using newspaper. This study discusses the representation of the Chinese Ethnic identity herald in Kompas. Obituaries not only contains a message that informing about obituary and feelings over the death of a family bereavement. However, the ad represents the identity of Chinesse community, so as to eliminate the descrimination over Chinesse community, such as the use of Chinesse letter also Chinesse name in public area. Chinese cultural identity represent various kinds of ornaments used in reporting the death in the newspaper. Roland Barthes semiotic method is used to analyze the obituary in the section on Media Kompas Klasika. Representation of Chinese culture through two levels of analysis, the first order of denotation and the second level is at the level of meaning, which means a second connotation and myth. Through this analysis knife, can find the deep process of obituary found in Kompas. The order of denotatif shows the history of the circle that indicates the ethnic Chinese through Chinese writing and the name written. In order of connotation, myth represented the culture and rituals of death. Conclution is mediated behaviors related to cultural identity which is looks from many aspects such us: photo, written, religion, culture and economic. The media type selected is the tendency of newspapers collaborative , fast and global. Keywords : Mediated Behaviors, Identity of Chinese Culture, Obituary, Print Media